Tummy Ache - (:unkn) unknown (Coy C. Carpenter Library, 1948)
Published in 1948 Gray and White Matter yearbook.
Doctor Dennis W. Biggs, Jr., originally of Lumberton, North Carolina, checks out a little patient at North Carolina Baptist Hospital in 1948.
Keywords: Forsyth County (N.C.) -- History -- Sources; Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works